Exploration of the Potential of Beetroot Betacyanin (Beta Vulgaris) As a Natural Dye to Replace Giemsa in Blood Smears (Indo-MathEdu Intellectuals Journal, 2026)
This study aimed to evaluate the effectiveness of betacyanin extract from red beetroot (Beta vulgaris) as a natural alternative to Giemsa stain in blood smear preparations. A quasi-experimental, descriptive-comparative approach was employed, using a single sample of peripheral blood from a healthy individual. The smears were stained using betacyanin extract adjusted to pH 3, 5, and 7, while a control sample was stained with 10% Giemsa. Staining outcomes were assessed based on four parameters: color intensity, cell morphology clarity, staining homogeneity, and color stability after 24 hours. Betacyanin was extracted using maceration with methanol-HCl solvent, followed by pH adjustment. Data were analyzed descriptively by comparing the mean staining-quality scores across pH variations with the Giemsa control. The results showed that Giemsa provided optimal performance across all parameters, with high intensity, excellent cell structure clarity, and consistent, stable coloration. Among the betacyanin treatments, pH 5 yielded the best performance, with relatively strong color intensity and moderate staining homogeneity, although it did not match the staining quality of Giemsa. In contrast, betacyanin at pH 3 and 7 produced lower staining quality, both in terms of contrast, distribution, and stability. This study concludes that betacyanin at pH 5 shows potential as a natural stain for hematological use, yet still requires further optimization